Effects of different intensity physical exercise on mental health of College Students - Yu, Ming; Wang, Xiaomei; Lu, Yang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
To investigate the effect of different intensities of physical exercise on the mental health of college students. This paper examines the impact of different intensities of physical exercise on the mental health of college students using the SCL-90 symptom checklist. The results of the intermediary effect analysis revealed that the P values of all indexes in the control group were greater than 0.05, indicating that there was no significant difference between the various indexes before and after the experiment and that the physical health did not improve significantly. The decrease of each index score in the control group was significantly less than in the experimental group, and the growth rate of paranoia reached 4.58 percent. Theoretically, the human body's psychological response and mental health will vary significantly depending on the intensity and frequency of physical activity.